The psychological well-being of disadvantaged youth in South Africa : an investigation into the use of an emotional intelligence workshop. - Smith, Lorandi (My University, 2013)
The legacy of apartheid in South Africa has contributed to the increase of psychological problems and stressors, especially in disadvantaged communities (Ruane, 2006). Literature surrounding adversity points out that well-being and the realising of the highest human good can be improved and should be studied in this population group. Psychological well-being is not just exclusively for the privileged segment of society (Ryff & Singer, 2008). Psychological health has many benefits that can add to the positive functioning of the disadvantaged youth in South Africa. The aim of this study was to determine whether emotional intelligence (EI) training could bring about an increase in psychological well-being (PWB) and trait emotional intelligence (TEI) for disadvantaged youth in South Africa. The study made use of a true experimental, pre-test - post-test design within which the effect of emotional intelligence training on PWB was investigated. The Ryff’s Psychological Well- being scale (PWBS) was implemented to determine the PWB of the participants, while the Trait Emotional Intelligence Questionnaire – Short Form (TEIQue-SF) was utilised to investigate TEI. The sample consisted of youth that were part of the “bridge the gap” programme within Oasis [a local Non Government Organisation (NGO)]. The “bridge the gap” programme runs over a six month period with the aim to equip youth with life skills to make them more employable. The sample size consisted of 63 individuals, both male and female, ranging in age from 18 to 27, who were randomly assigned to the experimental (n=32) and control groups (n=31). All participants were literate and fell within the same socio-economic class. Results indicated that the PWB of the experimental group improved, but not to the extent that the researcher had anticipated. Furthermore, results showed no improvement in TEI. The relationship between PWB and TEI was also explored, and it was found that a strong relationship exists between these two constructs. The present study aimed to add to the body of knowledge that exists in promoting PWB for disadvantaged youth, and thus amplify the necessity for programmes that do so. The study concludes with a discussion of its limitations and suggestions for future research in this specific area.
Keywords: Youth with social disabilities--South Africa--Psychology.; Emotional intelligence--Study and teaching--South Africa.